Coping strategies of HIV-positive individuals and its correlation with quality of life in Pune, India. (March 2016) - Kohli, Rewa; Sane, Suvarna; Ghate, Manisha; Paranjape, Ramesh
Quality of life including the domains of physical health and mental health are influenced by HIV infection. Coping strategies and their relationships with various domains of quality of life (QOL) were assessed among 97 HIV-infected individuals in Pune, India. Most of the infected individuals adopted emotion-focused strategies through cognitive reframing and acceptance of their HIV status. One-third adopted problem-focused coping and sought health care, scientific information and social support. Significant associations of coping strategies were observed with marital status and work and earning domains of the QOL questionnaire. Findings can help decide appropriate care and support strategies and psycho-social interventions for HIV-infected individuals.